Implementasi Strategi Pembelajaran Aktif pada Mata Pelajaran Pendidikan Agama Islam (PAI) - Dimas Saputra; Ahmad Azim; Gumaneli Gumaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to examine the implementation of active learning strategies in Islamic Religious Education (PAI) at the secondary school level. Active learning is an approach that emphasizes students’ direct participation, critical thinking skills, and collaborative interaction. This research employs a qualitative descriptive method through classroom observations, teacher interviews, and document analysis conducted at a school. The findings indicate that teachers have implemented various active learning strategies such as Think-Pair-Share, jigsaw, and role-playing. These strategies have been proven to enhance students’ engagement, motivation, and understanding of Islamic values. The study recommends continuous professional development for teachers as well as the integration of technology in the learning process.